PENGARUH MOTIVASI BELAJAR DAN PERSEPSI SISWA ATAS LAYANAN KONSELING TERHADAP PRESTASI BELAJAR PADA MATA PELAJARAN IPS - Evi Fitriyanti (Universitas Indraprasta PGRI, 2015)
One supporting student success in achieving optimal learning is by maintaining the motivation to learn which can be given through counseling services by teacher guidance and counseling as a counselor at school. The purpose of this study to determine the extent of the influence of students' learning motivation and perception on counseling services together on learning achievement in social studies. The method used was a survey by correlation and multiple regression techniques. The data and perceptions of students' learning motivation on counseling services obtained through the inventory, while data on student achievement in social studies obtained through leger. Research results through testing analysis showed that the correlation coefficient and the regression coefficient is significant, either jointly or individually partially. It is membukikan that there is significant influence, motivation to learn and perepsi counseling services to students on learning achievement in social studies subjects, either together or respectively. Keywords :Motivation; Perceptions; Counseling; Achievement Subject IPS